Inter-facility transfers in the Cape Town Metropole by the Western Cape Government Emergency Medical Service: A retrospective, descriptive study - Lemke, Franz (Division of General Surgery, 2024)
Background The South African health service is built upon a three-tier system, with the result that interfacility transfers (IFTs) are a cornerstone of a functional health ecosystem. Patients are transferred between facilities until their needs are met by the level of care provided. The Western Cape Government annual report of 2017/2018 states that 31.6 % of the workload of the Western Cape Government Emergency Medical Service (WCGEMS), is inter-facility transfers. Objectives This study describes the inter-facility, road-based transfers undertaken by the WCGEMS in the Cape Town metropole. We describe the number and type of transfers between health facilities as well as identifying the most common routes, prioritisation, crew make-up and acuity levels of patients transferred. Methods A retrospective, descriptive, observational study was conducted using the Cape Town Emergency Medical Service inter-facility transfer electronic database for the study period of 1 January 2017 to 31 December 2018. The existing database provided information logged routinely by EMS staff during each transfer and has been analysed using the statistical software Stata. Results Some 231,340 IFTs were included, of which two-thirds were undertaken by the day shift: 160,068 (69%) vs 71,272 (31%). Most emergency transfers were conducted for female patients [50,468 (62%) vs 31,468 (38%)]. Intermediate Life Support (ILS) crew facilitated most of the transfers 106,747 (51%) with Basic Life Support (BLS) crew in 53,165 (26%) and 48,534 (23%) by Advanced Life Support (ALS). The busiest route in the metro was identified as Khayelitsha (Site B) Community Health Centre (CHC) to Khayelitsha Hospital n=12,053, with some 17 transfers conducted per 24-hour period. The busiest routes, Khayelitsha CHC to Khayelitsha Hospital and Mitchells Plain CHC to Mitchells Plain Hospital were also the shortest, at 4.53 km and 2.78 km respectively. In totality, less than a third if IFTs [67,061 (30%)] required the use of stretchers. Conclusion IFTs are an integral part of the South African healthcare system, but the use of a frontline, EMS-driven model to provide IFTs is resource intensive and likely detrimental to overall EMS service delivery given the low acuity of the majority of patients transferred. Consideration should be given to creating, equipping, and adequately funding a separate service to take over responsibility for routine IFTs. This so-called ‘second leg' of EMS should be a dedicated, 24- hour, seven-day-week, low fidelity service, lessening the load on the frontline EMS resources and allowing first responders to focus on their main task—primary medical response.